Weak+Vacuum and One Decoy States with Two Way Quantum Key Distribution Protocol - Mohd Fared Abdul Khir; I. Bahari; S. Ali; S. Shaari (World Scientific Publishing Company, 2024)
Open Systems & Information Dynamics VOL. 20, NO. 02